Respuesta :
Hello,
--------4----3----2----1----0
.........1.....0.....1.....1.....-k
p=1..........1.....1.....2 ....3
.........1.....1.....2.....3.....0
==>-k+3=0==>k=3
--------4----3----2----1----0
.........1.....0.....1.....1.....-k
p=1..........1.....1.....2 ....3
.........1.....1.....2.....3.....0
==>-k+3=0==>k=3
Answer:
k = 3.
Step-by-step explanation:
If p-1 is a factor of the polynomial, that is
[tex]p^4+p^2+p-k = (p-1)q(p)[/tex]
with q(p) be another polynomial. Then with p=1 the polynomial is equal to 0. So,
[tex]1^4+1^2+1-k = 0[/tex]
[tex]1+1+1-k = 0[/tex]
[tex]3-k = 0[/tex]
[tex]k = 3[/tex].